2008
DOI: 10.1136/ard.2007.086777
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular function is impaired in ankylosing spondylitis and improves after tumour necrosis factor α blockade

Abstract: Objectives: Ankylosing spondylitis (AS) is associated with increased cardiovascular morbidity and mortality. Microvascular function has been linked to several risk factors for cardiovascular disease. Inflammation in AS may cause microvascular dysfunction. To test this, we assessed microvascular function in (a) patients with AS compared to healthy controls and (b) patients with AS before and after 1 month of anti-tumour necrosis factor (TNF)a treatment with etanercept. Methods: A total of 15 consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
2
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 50 publications
6
63
2
8
Order By: Relevance
“…A Dutch group analysed endothelial microvascular function in patients with AS before and after treatment with etanercept. They confirmed impaired microvascular function in AS patients compared to controls and also showed a significant improvement in some parameters following 1 month's treatment with etanercept [Van Eijk et al 2009]. Further data are needed to see if this improvement in microvascular function correlates with an improvement in ongoing cardiovascular risk.…”
Section: Safety Of Anti-tnf In Ankylosing Spondylitissupporting
confidence: 53%
“…A Dutch group analysed endothelial microvascular function in patients with AS before and after treatment with etanercept. They confirmed impaired microvascular function in AS patients compared to controls and also showed a significant improvement in some parameters following 1 month's treatment with etanercept [Van Eijk et al 2009]. Further data are needed to see if this improvement in microvascular function correlates with an improvement in ongoing cardiovascular risk.…”
Section: Safety Of Anti-tnf In Ankylosing Spondylitissupporting
confidence: 53%
“…19,20 Moreover, treatment with TNF-␣ antagonists is reported by a few small studies to improve endothelial function and aortic stiffness in patients with RA 11,21,22 and microvascular function in patients with AS. 14 Aortic pulse wave velocity (aPWV), a measure of aortic stiffness, is considered the current gold standard for measuring arterial stiffness. 9 The effect of treatment with TNF-␣ antagonists on aPWV in other inflammatory arthropathies than RA was, to our knowledge, not explored previously.…”
mentioning
confidence: 99%
“…In another study, the lower HDL cholesterol values were observed to be correlated with the intensity of the inflammation [25]. Van Eijk et al have observed in their study that the increases in the sedimentation rate and CRP values caused significant decreases in the HDL cholesterol levels [26]. Based on these results, it can be concluded that the cause of the lower HDL values in the patients with AS may play a partial role in the inflammation and the cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 80%